Particle swarm optimization for redundant building cooling heating and power system - Wang, Jiangjiang; Zhai, Zhiqiang (John); Jing, Youyin; Zhang, Chunfa (Applied energy, 2010)
An optimal and redundant building cooling heating and power (BCHP) system can yield economical savings, but more importantly can save energy as well as reduce the emission of pollutants. This paper presents the energy flow analysis of the conventional separation production (SP) system and the redundant BCHP system. Four decision variables (the capacity of power generation unit (PGU), the capacity of heat storage tank, the on–off coefficient of PGU and the ratio of electric cooling to cool load) to be optimized are selected in consideration of the design and the operation strategy of BCHP system. An objective function to simultaneously measure the energetic, economical and environmental benefits achieved by BCHP system in comparison to SP system is constructed and maximized. Particle swarm optimization algorithm (PSOA) is employed to search the optimal solutions. A case study of BCHP system with thermal storage unit and hybrid cooling system is presented to ascertain the feasibility and validity of the optimization method.